Destination image through the perspectives of travellers to state of Perak, Malaysia - Jamaludin, Mazlina; Mokhtar, Muhammad Fauzi; Aziz, Azlizam (Human Resource Management Academic Research Society, 2018)
In selecting tourism destination, travelers based their decisions on the perception of destination image attributes which they received from multiple information sources. Thus, the objective of this study was to explore and identify the dimension of image as perceived by travelers to the state of Perak, Malaysia by employing an exploratory factor analysis. The results exhibited that local attraction and facilities is the main indicator that attracts tourists to Perak followed by natural setting. The findings also showed the need for facilities maintenance and development of quality infrastructures and facilities while minimizing detrimental impacts on the natural surroundings. This study confirms that ‘affective construct’ of destination image is the highest indicator that attracted visitors to state of Perak. Henceforth, strategic image management should be in place in both designing and implementing advertising, promotional campaign and maintaining the infrastructure. Implications for marketing as well future development of tourism in Perak are discussed and presented in this paper.